2011
DOI: 10.1074/jbc.m111.252213
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protonation/Deprotonation of Tyrosine Residues in Cytochrome ba3 Oxidase from Thermus thermophilus by Time-resolved Step-scan Fourier Transform Infrared Spectroscopy

Abstract: Elucidating the properties of the heme Fe-Cu B binuclear center and the dynamics of the protein response in cytochrome c oxidase is crucial to understanding not only the dioxygen activation and bond cleavage by the enzyme but also the events related to the release of the produced water molecules. The time-resolved step-scan FTIR difference spectra show the 7a (CO) of the protonated form of Tyr residues at 1247 cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…12 There is, however, little direct evidence as the Y • would be antiferromagnetically (AF)-coupled to the Cu(II) and not detectable. 1316 …”
Section: Introductionmentioning
confidence: 99%
“…12 There is, however, little direct evidence as the Y • would be antiferromagnetically (AF)-coupled to the Cu(II) and not detectable. 1316 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Time-resolved step-scan FTIR spectroscopy has been utilized extensively in the ns-ms time range to probe the dynamics of ba 3 and oxidoreductase. [13][14][15][16][17][18][19][20][21][22] The presence of both protonated and deprotonated forms of the ring A of heme a 3 propionate and the deprotonated form of Asp372 has been determined by time-resolved Fourier transform infrared spectroscopy on the ba 3 -CO complex. 19 Based on recent Molecular Dynamics (MD) results, it was demonstrated that water molecules inside the protein are involved in the proton pumping activity as proton carriers and the highly conserved water molecule that lies between the heme a 3 propionates is capable of transferring its proton to propionate-A which affects the Fe oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…F transition in the ba 3 oxidase from T. thermophilus [64] despite that two protons are taken up by the ba 3 oxidase during this transition as in the case of the aa 3 oxidases [67]. That intermediate F II of ba 3 oxidase may retain the $610 nm absorption band of F I is also implied by recent work [65].…”
Section: The 607/580 Nm Transition In Ferryl-oxo Compounds Of Coxmentioning
confidence: 64%
“…The physical nature of the intense 607-610 nm absorption band in ''compounds P'' has not been established. Recent findings of a very similar band in the ''P R '' [64] and ''P M '' [65] intermediates of ba 3 oxidase from T. thermophilus, where the absorption of the low-spin heme b is well separated from the a-band of heme a 3 , confirm at least that the band indeed belongs to heme a 3 , and not to the low-spin heme a. As noted in [66] the narrowness of the a-band of ''P''-state at $607 nm may indicate that this form of heme a 3 is diamagnetic due to an uniaxial distortion of the heme plane sufficient to lower the energy of the d xz -orbital by the amount required to cause complete pairing of the four d-electrons of the ferryl heme iron.…”
Section: The 607/580 Nm Transition In Ferryl-oxo Compounds Of Coxmentioning
confidence: 95%